Determinants of bank closures: Do changes of CAMEL variables matter? - Mikko Mäkinen; Laura Solanko (Bank of Finland, Institute for Economies in Transition (BOFIT), 2017)
This study examines whether changes in CAMEL variables matter in explaining bank closure. Using a unique set of monthly bank-specific balance sheet data from Russia, we estimate determinants of bank license withdrawals during 2013m7-2017m7. We make two key findings. First, changes in CAMEL indicators are always significantly correlated with probability of bank closure, and the magnitude of parameter estimates decreases with the lag length. Second, while the one-month lagged levels of capital, earnings, and liquidity are significantly associated with the probability of bank closure in the subsequent month, the level of liquidity is the only significant indicator for longer lags. Our key contribution that changes in CAMEL variables matter more than levels is robust to various robustness checks.
URN:NBN:fi:bof-201710301659
Keywords: G01; G21; G32; G34; 330